Effects of Potassium Fulvic Acid on Soil Physical and Chemical Properties and Soil Microenvironment of Blueberry (Vaccinium corymbosum L.) Under Salt Stress - Xuanrong Wu; Dekang Hou; Jing Ma; Yanan Li; Lin Wu; Haiguang Liu; Yi Zuo; Xinxin Guo; Jinying Li; Ying Wang (Plants)
These days, one of the main issues preventing agricultural development is salinized soils. Potassium fulvic acid (PFA) not only regulates plant growth, but also improves the soil nutrient content and physical structure, which makes it a soil conditioner worth promoting. Nevertheless, the research conducted thus far on the subject of PFA with regard to plant growth and inter-root microbial communities remains somewhat limited in scope. In this study, a pot experiment was conducted to simulate both the normal environment and salt stress environment. The objective of this experiment was to verify the effect of PFA on the growth of blueberry (Vaccinium corymbosum L.) as well as its effect on the soil physical and chemical indices and the soil microbial community structure. The findings demonstrated that the implementation of potassium fulvic acids exhibited a minimal impact on the growth of blueberry plants under standard environmental conditions. However, it was observed to exert a substantial effect on enhancing various physiological parameters, including plant height, root activity, and chlorophyll synthesis, particularly in response to salt stress. PFA led to a substantial augmentation in the soil organic matter content, alongside a notable rise in the alkali-hydrolyzable nitrogen (AN) and available potassium (AK) content. Concurrently, PFA caused a notable escalation in the activities of soil urease, sucrase, acid phosphatase, and catalase (p < 0.05) in the salt-stressed environment. PFA increased the abundance of Acidobacteria, Myxococcota, Ascomycota, and Fungi_phy_Incertae_sedis under salt stress, which was mainly related to the decrease in electrical conductivity (EC) values and increase in soil acid phosphatase (S-ACP) activity. It is evident that the implementation of PFA is advantageous in enhancing the saline environment, mitigating the impact of salt damage on blueberries and establishing a foundation for the expansion of cultivated areas and the sustainable cultivation of blueberries.